2019
DOI: 10.1177/0306624x19853110
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Risk Profiles of Australian Young Offenders From Rural and Urban Communities

Abstract: Australian young people from rural areas, particularly Aboriginal young people, are overrepresented in the juvenile justice system. Apart from broad evidence regarding the entrenched social disadvantages experienced by young people in rural communities, the literature is limited in describing why this might be case. Due to these social disadvantages, it is hypothesised that young offenders from rural communities will have higher levels of offending risk factors, as measured by the Youth Level of Service/Case M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Information about where young people who offend lives is of particular importance to any attempt to achieve these targets, given that 41% of Aboriginal young people who are under the supervision of youth justice services come from regional, remote, or very remote communities while only 8% of non-Aboriginal youth come from these areas (Australian Institute of Health & Welfare, 2018). The importance of this is highlighted in data reported by Butcher et al (2019) which shows that Aboriginal young people in New South Wales (NSW) who had offended for the first time were more likely to come from rural of areas despite having lower levels of assessed risk and need than their urban counterparts. For Butcher et al, this suggests that any policy that aims to address the over-representation of Aboriginal rural young people will need to be cognisant of the unique context and structure of each community, rather than simply importing population health interventions from other parts of the world.…”
Section: The Over-representation Of Aboriginal Young People From Rura...mentioning
confidence: 99%
See 1 more Smart Citation
“…Information about where young people who offend lives is of particular importance to any attempt to achieve these targets, given that 41% of Aboriginal young people who are under the supervision of youth justice services come from regional, remote, or very remote communities while only 8% of non-Aboriginal youth come from these areas (Australian Institute of Health & Welfare, 2018). The importance of this is highlighted in data reported by Butcher et al (2019) which shows that Aboriginal young people in New South Wales (NSW) who had offended for the first time were more likely to come from rural of areas despite having lower levels of assessed risk and need than their urban counterparts. For Butcher et al, this suggests that any policy that aims to address the over-representation of Aboriginal rural young people will need to be cognisant of the unique context and structure of each community, rather than simply importing population health interventions from other parts of the world.…”
Section: The Over-representation Of Aboriginal Young People From Rura...mentioning
confidence: 99%
“…The importance of this is highlighted in data reported by Butcher et al. (2019) which shows that Aboriginal young people in New South Wales (NSW) who had offended for the first time were more likely to come from rural of areas despite having lower levels of assessed risk and need than their urban counterparts. For Butcher et al., this suggests that any policy that aims to address the over‐representation of Aboriginal rural young people will need to be cognisant of the unique context and structure of each community, rather than simply importing population health interventions from other parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…These differences may relate to organizational issues (e.g., the recruitment of staff or the availability of resources in the community) as well as to the characteristics of people. For example, a recent study reported that young people in a geographically remote part of Australia were, on average, at a lower risk of reoffending than those in the metropolitan area (Butcher et al, 2019). In considering the characteristics of people under supervision that are likely to be associated with effective community supervision outcomes, there is evidence that high-risk people who receive more intensive supervision benefit the most (i.e., adherence to the risk principle; see Bourgon et al, 2010), given that risk is associated with many personal characteristics, including age, type of offense, and criminal history.…”
Section: A Theoretical Model Of Changementioning
confidence: 99%
“…These programs aim to reduce involvement with the justice system by addressing the presence or intensity of empirically derived risk factors thought to be associated with offending behaviour (Day & Fransisco, 2013; Poyton & Menendez, 2015; Stewart et al., 2014; Trimboli, 2019). However, recent evidence has shown significant differences between standardised risk profiles of Aboriginal young people who offend from rural, regional and remote areas and their metropolitan counterparts, thus drawing attention to the influence of ecology has on offending risk patterns (Butcher et al., 2019). A potential explanation for the apparent lack of progress being made in reducing over-representation is that current youth justice programs are not a sufficiently good fit to the contexts of Aboriginal rural young people, and therefore, have a low level of ecological validity (see H. Blagg, et al., 2015; Gray & Hetherington, 2007; Lavery, 2018).…”
mentioning
confidence: 99%